2002
DOI: 10.1002/ajhb.10077
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal clues apparently distinguishing Waldenstrom's macroglobulinemia from multiple myeloma and leukemia

Abstract: This study was conducted to characterize macroscopically and by conventional radiography the bony lesions in a case of Waldenstrom's macroglobulinemia and to compare and contrast it with those of the other major hematologic lymphoproliferative disorders, multiple myeloma and leukemia. Two varieties of lytic skeletal lesions were found in Waldenstrom's macroglobulinemia. One was sharply defined, spheroid lesions with smooth borders and effaced/erased trabeculae. The second was in the form of coalescing pits (ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Analyses that focus on differential diagnoses that include leukemia are scarce in the review of archaeological remains (Klaus, ; Rothschild et al, ; Rothschild, Ruhli, & Rothschild, ). Moreover, some of these articles relied on contemporary skeletal collections in which the cause of death was known (Rothschild et al, ; Rothschild et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Analyses that focus on differential diagnoses that include leukemia are scarce in the review of archaeological remains (Klaus, ; Rothschild et al, ; Rothschild, Ruhli, & Rothschild, ). Moreover, some of these articles relied on contemporary skeletal collections in which the cause of death was known (Rothschild et al, ; Rothschild et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Analyses that focus on differential diagnoses that include leukemia are scarce in the review of archaeological remains (Klaus, 2016;Rothschild et al, 1997;Rothschild, Ruhli, & Rothschild, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postmortem studies reported in the literature revealed bony changes including lytic lesions without bony resorption. 16 The left dyschromatopsia and afferent pupillary defect in this patient likely represent compressive optic neuropathy because of the intraorbital portion of the mass.…”
mentioning
confidence: 80%
“…This malignancy is thought to originate from a B cell stimulated to differentiate to a plasma cell that has been exposed to the germinal centre environment. Lytic bone disease is very uncommon in WM (Rothschild et al, 2002). However, abnormal bone remodelling close to malignant cells, characterised by increased bone resorption and normal or reduced bone formation that leads to microresorption lesions, has been described in almost 80% of WM patients in bone histomorphometric studies (Marcelli et al, 1988).…”
mentioning
confidence: 99%